Magnetic nanoparticles utilized in hemodialysis for the treatment of hyperhomocysteinemia: The new challenge of nanobiotechnology - Stamopoulos, D. (CURRENT NANOSCIENCE, 2008)
Owing to vast technological advances, hemodialysis (HD) has become a mature modality significantly increasing the survival of end-stage renal disease (ESRD) patients. However, many HD complications still exist that mainly relate to the nature of middle-molecular-weight and/or protein-bound toxins that both low- and high-flux dialysers cannot efficiently remove. For instance, hyperhomocysteinemia and amyloidosis are two dialysis-related disorders that motivate serious health complications. Here, we introduce a new method for the selective removal of specific toxins that is based on the preparation of Ferromagnetic Nanoparticle-Targeted Binding Substance Conjugates (FN-TBS Cs) constituted of biocompatible FNs and a specifically designed TBS that must have high affinity for the respective Target Toxin Substance (TTS). The FN-TBS Cs should be administered to the patient timely prior to the dialysis session so that they will be able to bind with the specific TTS owing to their free circulation in the bloodstream. The complex FN-TBS-TTS can be selectively removed from the ESRD patient during the HD session by means of a magnetic dialyser (MD). For the in vitro evaluation of this proposal we employed highly biocompatible Fe3O4 and Bovine Serum Albumin (BSA) as constituents of the FN-TBS Cs and an array of permanent magnets placed along the circulation line as a simple MD. We have evaluated the binding affinity and capacity of both bare Fe3O4 FNs and Fe3O4-BSA Cs by employing homocysteine (Hcy) as a model TTS. We investigate Hcy concentrations ranging from mild to severe hyperhomocysteinemia. Most importantly, we investigate the effectiveness of low concentrations of Fe3O4 that are within the safety levels established from the treatment of iron-deficiency anemia, thus making a preliminary evaluation of future in vivo applications. We observed that Hcy is readily adsorbed onto both bare Fe3O4 FNs and Fe3O4-BSA Cs. The obtained results prove the successful in vitro applicability of the proposed method since pathological Hcy concentrations may be adequately handled by relatively low Fe3O4 concentrations, thus making feasible future in vivo applications.